Preparation and characterization of aqueous polyurethane oil/polyacrylate latex interpenetrating polymer network. Issue 1 (June 2015) - Zhou, M M; Ma, L L; Du, J; Cao, F; Xiao, J J
Abstract: A series of aqueous polyurethane oil (network I)/polyacrylate (network II) latex interpenetrating polymer networks (LIPNs) were synthesized via the technology of latex interpenetrating polymer network combined seed emulsion polymerization process. Fourier transform infrared (FTIR) spectroscopy, laser particle size distributing analyzer and universal tension machine were utilized to characterize the bulk structures and mechanical properties of LIPNs. For used as damping material, the damping performance of LIPNs were analyzed by dynamic mechanical analysis (DMA). It was found that the damping temperature region of LIPN was wider than those of aqueous polyurethane oil, the temperature region with greater tanδ changed with the TPGDA content and hard-/soft-segment mass weight ratio ( m MMA / m BA ) and the glass transition temperature (Tg ) of the network I and network II in LIPN occurred within shift each other, even overlap with increasing m MMA / m BA value. The results show that LIPNs synthesized through the combined process have greater tanδ and wider damping temperature region, which is suitable for the use of damping coatings.